Reliability and Validity of the Instrument Assessing the Effectiveness of Online and Regular Classroom Lessons - Ranđelović, Dušan J.; Lazarević, Dragana Đ.; Pavićević, Miljana S. (Collection of Papers of the Faculty of Philosophy in Priština, 2022)
In order to propose a new instrument for evaluating the efficiency of teaching process, this paper presents the recently designed tool called Online and Classroom Teaching Efficiency Scales – OCTES. It strives to examine reliability and validity of the OCTES scale on a sample of students (N1=100) and teachers (N2=100). The instrument used to evaluate the effectiveness of three aspects of teaching in two teaching scenarios—classroom teaching and online teaching— includes 3 scales related to cognitive, conative, and affective aspects of teaching. The results indicated that all scales have high reliability (over .80 Cronbach’s alpha) on both the teacher subsample and the student subsample. The construct validity was verified by exploratory factor analysis. The results have confirmed that one-factor solutions are acceptable for all measured scales, with the explained variation ranging from 41.13% during the assessment of the affective component of classroom teaching, to 64% during the assessment of conative aspects of classroom teaching. It can be inferred that the final version of the 30-item scale showed good psychometric properties reflected in high reliability of all assessed aspects of teaching efficiency and solid validity seen through one-factor structure of all scales.